Murder in the dark: Can parasites bring jellyfish blooms to fall? - Nicole Aberle; Torkild Bakken; Luis Martell; Pedro R. De La Torre; Kay Arne Skarpnes; Erling Svensen; Sanna Majaneva (Fauna Norvegica)
Jellyfish form irregular and seemingly unpredictable blooms that can be the result of redistribution/aggregation events or peaks in population growth. Such blooms can affect ecosystem structure and stability due to the role of jellyfish as top predators of fish larvae and eggs and as competitors of fish preying on the same zooplankton resources. Factors leading to jellyfish bloom formation have received a lot of attention during the past decades. However, factors causing blooms to collapse are less studied. The helmet jellyfish Periphylla periphylla is a bloom-forming jellyfish species that shows mass occurrences in several Norwegian fjords with substantial socioeconomic implications. The success of P. periphylla to form massive blooms is attributed to its longevity, the lack of natural predators and its holoplanktonic life cycle with a continuous reproduction throughout the year. In Trondheimsfjorden, central Norway, P. periphylla has established large populations over the last decades. However, population estimates with a high spatiotemporal resolution are scarce and the regulating mechanisms affecting P. periphylla dynamics remain largely unknown. Using in-situ imaging techniques during pelagic dives with a remotely operated vehicle (ROV), enabled insights  on the potential role of parasites as bloom-controllers. ROV footage provided unique information on high levels of prevalence and intensity of parasitic amphipods in P. periphylla. In parallel, these parasitic associations were documented by underwater  photography in the same area and season. The combination of non-invasive imaging techniques allowed estimates on the degree of parasite infestation and on how parasitism can affect the condition of jellyfish populations thus eventually causing blooms to  collapse. We suggest taking investigations on parasite-host interactions and the role of parasitism as a population control  mechanism into the spotlight. Future research in this field will benefit from using non-invasive imaging tools to study parasite-host interactions and animal behaviour in-situ.